Effect of Ecdysial Cycle on the Semen and Spermatophore production of the Indian White Prawn (Penaeus indicus H.M. Edwards) - A.L., Muthuraman (Fishery Technology, 2025)
Adult male Penaeus Indicus have a prolonged premolt phase and short inter and postmolt phases in its ecdysial cycle. Vas deferens factor and spermatophore weight of male prawns show a declining tendency from post to premolt phases with a successive reduction in the biochemical composition of vas deferens and terminal ampoule. The correlation analysis indicate differential intensity of coefficients between biochemical and morphometrical relationships of semen and spermatophore production of P. Indicus.